Two distinct secretion systems facilitate tissue invasion by the rice blast fungus Magnaporthe oryzae - Giraldo, Martha C.; Dagdas, Yasin F.; Gupta, Yogesh K.; Mentlak, Thomas A.; Yi, Mihwa; Martinez-Rocha, Ana Lilia; Saitoh, Hiromasa; Terauchi, Ryohei; Talbot, Nicholas J.; Valent, Barbara (My University, 2013)
To cause plant diseases, pathogenic micro-organisms secrete effector proteins into host tissue to suppress immunity and support pathogen growth. Bacterial pathogens have evolved several distinct secretion systems to target effector proteins, but whether fungi, which cause the major diseases of most crop species, also require different secretory mechanisms is not known. Here we report that the rice blast fungus Magnaporthe oryzae possesses two distinct secretion systems to target effectors during plant infection. Cytoplasmic effectors, which are delivered into host cells, preferentially accumulate in the biotrophic interfacial complex, a novel plant membrane-rich structure associated with invasive hyphae. We show that the biotrophic interfacial complex is associated with a novel form of secretion involving exocyst components and the Sso1 t-SNARE. By contrast, effectors that are secreted from invasive hyphae into the extracellular compartment follow the conventional secretory pathway. We conclude that the blast fungus has evolved distinct secretion systems to facilitate tissue invasion.
Citation: Giraldo, M., . . ., Valent, B. (2013). Two distinct secretion systems facilitate tissue invasion by the rice blast fungus Magnaporthe oryzae. Nature Communications, 4, 1996. https://doi.org/10.1038/ncomms2996
Keywords: Magnaporthe oryzae; Rice blast disease; Effector proteins